2020
DOI: 10.1101/2020.06.03.131490
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

C. eleganspharyngeal pumping provides a whole organism bio-assay to investigate anti-cholinesterase intoxication and antidotes

Abstract: 34Inhibition of acetylcholinesterase by either organophosphates or carbamates causes anti-35 cholinesterase poisoning. This arises through a wide range of neurotoxic effects triggered by the 36 overstimulation of the cholinergic receptors at synapses and neuromuscular junctions. Without 37 intervention, this poisoning can lead to profound toxic effects, including death, and the incomplete 38 efficacy of the current treatments, particularly for oxime-insensitive agents, provokes the need to find 39 better antid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(28 citation statements)
references
References 62 publications
3
25
0
Order By: Relevance
“…This assay has been extensively used to find molecular determinants at the NMJ of the body wall on the basis of resistance or hypersensitivity to paralysis of locomotion when nematodes are incubated on aldicarb-containing agar plates (26). We previously demonstrated that aldicarb and other cholinesterase inhibitors also cause a dose-dependent inhibition of the pharyngeal function (28). This inhibition was associated with the pharynx exhibiting hypercontraction observed by the opening of the lumen (28).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This assay has been extensively used to find molecular determinants at the NMJ of the body wall on the basis of resistance or hypersensitivity to paralysis of locomotion when nematodes are incubated on aldicarb-containing agar plates (26). We previously demonstrated that aldicarb and other cholinesterase inhibitors also cause a dose-dependent inhibition of the pharyngeal function (28). This inhibition was associated with the pharynx exhibiting hypercontraction observed by the opening of the lumen (28).…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that aldicarb and other cholinesterase inhibitors also cause a dose-dependent inhibition of the pharyngeal function (28). This inhibition was associated with the pharynx exhibiting hypercontraction observed by the opening of the lumen (28). This implied that aldicarb intoxication in the context of the whole organism would result from drug-induced hyperactivation of the cholinergic transmission.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations